Computer controlled expansion of equine cord blood mesenchymal stromal cells on microcarriers in 3 L vertical-wheel® bioreactors - Roberts, E. L.; Abraham, B. D.; Dang, T.; Gysel, E.; Mehrpouyan, S.; Alizadeh, A. H.; Koch, T. G.; Kallos, M. S. (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stromal cells (MSCs) are an ideal cell source for allogenic cell therapy due to their immunomodulatory and differentiation properties. Equine MSCs (eMSCs) have been found to be a promising treatment for equine joint injuries including meniscal injuries, cartilage degradation, and osteoarthritis. Although the use of eMSCs has shown efficacy in preliminary studies, challenges associated with biomanufacturing remain. To achieve the required cell numbers for clinical application, bioreactor-based processes are required. Initial studies have shown that eMSCs can be cultivated in microcarrier-based, stirred suspension bioreactor culture at the laboratory 0.1 L scale using a Vertical-Wheel® (VW) bioreactor. However, investigations regarding scale up of these processes to the required biomanufacturing scales are required. This study investigated the scale-up of a equine cord blood MSC (eCB-MSC) bioprocess in VW bioreactors at three scales. This included scale-up from the 0.1L to 0.5L bioreactor, scale-up from static culture to the 3L computer-controlled bioreactor, and scale-up into the 3L computercontrolled bioreactor using a mock clinical trial process. Results from the various scale-up experiments demonstrated similar cell expansion at the various tested scales. The 3L computercontrolled system resulted in a final cell densities of 1.5x10 5 cells/cm 2 on average, achieving 1.5x10 9 harvested cells. Biological testing of the cells showed that cell phenotype and functionality were maintained after scale-up. These findings demonstrate the scalability of an eCB-MSC bioprocess using microcarriers in VW bioreactors to achieve clinically relevant cell numbers, a critical step to translate MSC treatments from research to clinical applications. This study also represents the first known published study expanding any cell type in the 3L VW bioreactor.